Perfil epidemiológico e espacial das hepatites B e C em um município da Amazônia brasileira entre os anos de 2019 a 2021 - GOMES, Samara Azevedo (2024)
Viral hepatitis are diseases caused by different etiological agents, ranging from asymptomatic to fulminant presentation. More than 70% of notified cases of viral hepatitis compete with hepatitis B (HBV) and C (HCV) viruses, being responsible for the greatest social and economic impact, due to the likelihood of progression to other potentially fatal diseases. Thus, it was intended to investigate the epidemiological profile and spatial distribution of cases of viral hepatitis B and C in a municipality in the Brazilian Amazon in the period between 2019 and 2021. This was an ecological and descriptive population-based study of Altamira in the state of Pará, Xingu region - Brazilian Amazon, using secondary data from cases of carriers of viral hepatitis and their relationship with urban reorganization and population dynamics, in addition to the use of geoprocessing in the evaluation of the existence of micro-regions with a higher incidence of cases and relative spatial risk. Among the years studied, it was observed that 94% of notifications belong to the urban area, where the year 2019 presented 55.2% of confirmed cases of hepatitis B and C. There was an incidence of 57.5% of males, and a representativeness of 66.6% aged over 40 years was noted in relation to all confirmed cases. As a clinical form, 65.6% of the cases were predominantly related to chronic hepatitis. Through geoprocessing, it was observed that the greatest density in the investigated radius was up to 4 cases for hepatitis B and C, characterizing themselves as areas of risk and of greater attention for screening, surveillance and monitoring in the municipality. Through all the study carried out, and considering that Brazil is committed to adopting the objectives proposed by the World Health Organization to eradicate new cases of hepatitis B and C by 2030, it is concluded that there is a need for the development of original studies which aim at a better understanding of the clinical and epidemiological presentation of hepatitis B and C in the practical assistance experience of each Brazilian Region and State, with the purpose of more effectively tracing interventions in public and sanitary health for their eradication.